State of the Art: Management of Barrett's Esophagus Related Dysplasia and Neoplasia—Which Patient and What Therapy?. Issue 1 (March 2021) - Dhaliwal, Lovekirat; Iyer, Prasad G.
Endoscopic eradication therapy (EET) is safe and effective in the management of Barrett's esophagus (BE) related dysplasia and early adenocarcinoma. EET includes endoscopic resection of the visible lesions followed by ablation to eradicate the residual Barrett's epithelium. Techniques available for endoscopic resection include cap-based endoscopic mucosal resection and endoscopic submucosal dissection. Ablative therapies such as RFA, cryoablation and APC are used for the eradication of dysplastic BE and to prevent progression to EAC. Complete remission of intestinal metaplasia is the goal of EET. Post-treatment endoscopic surveillance is recommended to detect recurrence of metaplasia/dysplasia, mostly at the gastroesophageal junction.